MULTI STAKEHOLDER COLLABORATION IN IMPLEMENTING POVERTY ALLEVIATION POLICIES IN KENDARI CITY, SOUTHEAST SULAWESI - Tadung, Edy; Alwi; Gita Susanti (Master Program of Sociology, Universitas Malikussaleh,, 2025)
This study examines the practice of multi-stakeholder collaboration in the implementation of policies by the Kendari City Government in Southeast Sulawesi Province, which established the Regional Poverty Reduction Coordination Team (TKPKD). This collaborative practice is then formulated as a framework for the characteristics or key elements of sustainable collaboration. A case study methodology was used to explore various types of data for this case study of multi-stakeholder collaboration practices in Kendari City.Data were collected from sources that are more qualitative in character through documentary analysis, in- depth interviews, direct observations and field visits. The in-depth interview framework was developed through detailed documentary analysis. Open-ended and semi- structured duplication with stakeholders to achieve the goal of understanding TKPKD collaboration practices in the implementation of poverty alleviation policies. The results of the study indicate that multi-party collaboration practices in a series of interacting TKPKD institutional conditions can lead to sustainable transformation by implementing the main characteristics or elements of collaboration, namely stakeholder involvement, government roles, social learning, institutional capacity and collaborative leadership which when conceptualized will ultimately lead to transformation in the implementation of sustainable poverty alleviation policies.